2008
DOI: 10.1111/j.1939-1676.2008.0054.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Selenium and Vitamin E Supplementation of Weaned Beef Calves

Abstract: Background: The weaning process in beef calves elicits physiological stress responses that can negatively affect performance and health. Supplementation of vitamins and minerals, particularly selenium (Se) and vitamin E, might be warranted.Hypothesis: That parenteral administration of Se or vitamin E would correct or prevent deficiencies of these nutrients in postweaned beef calves during a backgrounding period (42 days after weaning).Animals: One hundred and forty-four weaned steers (200-250 kg) in 3 trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
3
6
1
1
Order By: Relevance
“…Similar result was also reported from an experiment conducted in lambs from a flock with white muscle disease history concerning to average daily gain [28]. In beef calves Se and vit E injection on days 0 and 28 of experiment had not significant effects on calf performance during the study [29]. In contrast, Se supplementation as inorganic or organic forms for 90 days caused better average daily gain in male lambs [12,30].…”
Section: Discussionsupporting
confidence: 91%
“…Similar result was also reported from an experiment conducted in lambs from a flock with white muscle disease history concerning to average daily gain [28]. In beef calves Se and vit E injection on days 0 and 28 of experiment had not significant effects on calf performance during the study [29]. In contrast, Se supplementation as inorganic or organic forms for 90 days caused better average daily gain in male lambs [12,30].…”
Section: Discussionsupporting
confidence: 91%
“…Probably this practice is more common in herds with calfhood problems, aiming to compensate for poor health by boosting nonspecific immunity. However, the effect of a single vitamin injection, which is the most common practice of providing vitamins to young calves in Estonian dairy farms, to the knowledge of the authors, might not yield significantly better health outcomes [42,43]. However, Torsein et al [5] found that fat-soluble vitamins might play an important role for calf health and possibly survival rates.…”
Section: Risk Factors Associated With Calf Mortality Ratementioning
confidence: 99%
“…Likewise, the use of injectable vitamin E and Se in prepartum dairy cattle enhanced antioxidant capacity [ 20 ] and decreased the incidence of postpartum mastitis [ 21 ]. However, average weight gain (AWG) was not improved in weaning calves [ 22 ]. Whereas oral vitamin E supplementation improved the health of calves at feedlot entrance [ 23 ], parenteral vitamin E (1 mg/kg) and Se (0.1 mg/kg) supplementation improved immunoglobulin G titers against Mannheimia haemolytica in shipping-stressed calves [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported different results regarding the utilization of parenteral supplementation of beef cattle with minerals and vitamins. Swecker et al [ 22 ] evaluated the effects of Se and vitamin E separately or combined, without finding a significant effect on calf growth rate. Arthington et al [ 14 ], using three consecutive intramuscular supplementations of trace minerals (Zn, Mn, Cu, and Se), showed that they increased Cu and Se status without affecting calf BW gain, but increased heifer BW gain and humoral immune response.…”
Section: Introductionmentioning
confidence: 99%